Risk perception of emergency medical technicians in biological disasters: a comparison between COVID-19 and Non-COVID-19 cases - Mohammad Azim Mahmodi; Ayob Akbari; Seyyed Mohammad Reza Hosseini; Zahra Amouzeshi (BMC Emergency Medicine)
Abstract Background Emergency medical technicians (EMTs), positioned at the forefront of medical services, are at greater risk of contracting COVID-19 and passing it on to their families and communities than others. Recognizing the risks associated with this disease can play a crucial role in the care and prevention process. Consequently, this study evaluated the level of risk perception (RP) regarding COVID-19 among EMTs and compared it between those who have contracted the disease and those who have not. Methods This was a cross-sectional descriptive-analytical study conducted in 2021. This study employed simple random sampling to select 200 EMTs affiliated with Birjand University of Medical Sciences. The sample included 100 EMTs who had contracted COVID-19 and 100 who had not. Data were collected through a researcher-designed questionnaire, distributed online via WhatsApp and Telegram groups among the participants. The data were analyzed using SPSS version 16, utilizing descriptive statistical methods (frequency, mean, and standard deviation) along with inferential statistical tests such as independent t-tests, chi-square, and two-way analysis of variance (ANOVA). Results The infected EMTs exhibited a moderate perception of the risk of COVID-19, while the non-infected EMTs reported a high level of RP. The independent t-test confirmed that the mean total score for COVID-19 RP was significantly lower in the infected EMTs compared to the non-infected group (mean RP score: infected 150.82 ± 32.24 vs. non-infected 161.54 ± 22.50, P = 0.007). Additionally, ANOVA revealed that none of the demographic variables individually had a significant impact on the level of COVID-19 RP (P > 0.05). Furthermore, the interaction effect between the demographic variables and the groups was also insignificant (P > 0.05). Conclusion EMTs who contracted COVID-19 had a significantly lower RP compared to their non-infected counterparts. This reduced awareness of COVID-19 risks likely contributed to their infection, highlighting the critical role of RP in disease prevention. Targeted educational programs to enhance RP among EMTs could foster stronger adherence to preventive measures, ultimately reducing infection rates during future biological disasters. Therefore, this study not only contributes to expanding existing knowledge in this field but also assists policymakers and health administrators in improving decision-making to strengthen epidemic preparedness.